N-fertilization and disturbance exert long-lasting complex legacies on subarctic ecosystems - Manninen, Outi H.; Myrsky, Eero; Tolvanen, Anne; Stark, Sari (Springer Nature, 2024)
Subarctic ecosystems are subjected to increasing nitrogen (N) enrichment and disturbances that induce particularly strong effects on plant communities when occurring in combination. There is little experimental evidence on the longevity of these effects. We applied N-fertilization (40 kg urea-N ha−1 year−1 for 4 years) and disturbance (removal of vegetation and organic soil layer on one occasion) in two plant communities in a subarctic forest-tundra ecotone in northern Finland. Within the first four years, N-fertilization and disturbance increased the share of deciduous dwarf shrubs and graminoids at the expense of evergreen dwarf shrubs. Individual treatments intensified the other’s effect resulting in the strongest increase in graminoids under combined N-fertilization and disturbance. The re-analysis of the plant communities 15 years after cessation of N-fertilization showed an even higher share of graminoids. 18 years after disturbance, the total vascular plant abundance was still substantially lower and the share of graminoids higher. At the same point, the plant community composition was the same under disturbance as under combined N-fertilization and disturbance, indicating that multiple perturbations no longer reinforced the other’s effect. Yet, complex interactions between N-fertilization and disturbance were still detected in the soil. We found higher organic N under disturbance and lower microbial N under combined N-fertilization and disturbance, which suggests a lower bioavailability of N sources for soil microorganisms. Our findings support that the effects of enhanced nutrients and disturbance on subarctic vegetation persist over decadal timescales. However, they also highlight the complexity of plant–soil interactions that drive subarctic ecosystem responses to multiple perturbations across varying timescales.
Keywords: treeline ecotone; plant recovery; functional types; microbial nitrogen; vegetation change